2017
DOI: 10.1002/pc.24698
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fiber concentration on fiber orientation in injection molded film gated rectangular plates

Abstract: Fiber orientation in film gated injection‐molded rectangular plates was characterized using micro computed tomography. Polyamide 12 materials with 15, 30, and 50 wt% glass fibers were used in this study. For all three materials, the typical core‐shell layer structure of fiber orientation was observed, but several features of the fiber orientation were highly dependent on the fiber content. Increasing fiber content resulted in increasing core layer thickness and a higher degree of orientation in the shell layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 29 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…In particular when one sets N p = 0, we retrieve the uncoupled scalar viscosity model, completely independent of fiber evolutions during the injection process. Since traditional linear dependence of N p on volume fraction may not be suitable for concentrated fiber-reinforced suspensions, see Jørgensen et al (2017), in this paper we adopt the nonlinear functional dependence of N p on fiber aspect ratio and volume fraction proposed by Phan-Thien and Graham (1991). Its dependence on mass fraction is illustrated in Fig.…”
Section: Anisotropic Fiber-induced Rheological Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular when one sets N p = 0, we retrieve the uncoupled scalar viscosity model, completely independent of fiber evolutions during the injection process. Since traditional linear dependence of N p on volume fraction may not be suitable for concentrated fiber-reinforced suspensions, see Jørgensen et al (2017), in this paper we adopt the nonlinear functional dependence of N p on fiber aspect ratio and volume fraction proposed by Phan-Thien and Graham (1991). Its dependence on mass fraction is illustrated in Fig.…”
Section: Anisotropic Fiber-induced Rheological Equationsmentioning
confidence: 99%
“…Since the core region is in general dominated by extensional flows transverse to the filling direction, it can be argued that these elongational deformations are not correctly taken into account in current models and a flow-fiber coupled simulation with fiber-dependent rheological properties may be more appropriate, cf. Tucker III (1991); Jørgensen et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…The fiber content also influences the ductility. A higher fiber content will lead to a decrease in ductility, with an increase in rigidity and strength 3,6 …”
Section: Resultsmentioning
confidence: 99%
“…The principal factor that affects the mechanical properties of SFRP is the fiber orientation. There are many factors that affect the fiber orientation such as injection point position, injection speed, injection pressure, mold temperature, fiber content, part geometry, and overall thickness 1–4 . Many studies are conducted to present the effects of fiber orientation on to the mechanical response of composite materials 5–21 …”
Section: Introductionmentioning
confidence: 99%
“…Using X‐ray computed tomography (X‐CT) removes the directional ambiguity arising from fiber orientation measurements performed using two‐dimensional techniques . Measurements of shell–core fiber orientation development in injection molded parts have already been performed using X‐CT for studies on mechanical properties . Recently, X‐CT study was shown as a viable technique for tracking 3D fiber orientation evolution during simple shear .…”
Section: Introductionmentioning
confidence: 99%